A Safer Housing Agenda for Women: Local Urban Planning Knowledge and Women's Grassroots Movements in Medellín, Colombia. (8th July 2020) - Gutiérrez Rivera, Lirio
Abstract: This essay looks at the process through which women's grassroots movements in Medellín, Colombia, were effective in ensuring that a gender perspective was incorporated into the city masterplan with the aim of making Medellín a safer city for women. Drawing on interviews with activists of the Mesa de Trabajo Mujer de Medellín (MTMM), one of the largest networks among women's grassroots movements, and interviews with officials working at the Office of the Secretary for Women and the Department of Planning, I argue that women's grassroots movements are actors in the urban planning process in Medellín. Focusing on the MTMM's agenda for safer housing, I show how the house represents a process that involves women's knowledge, relationships and experience. Furthermore, I show how housing acquires political meaning, becoming the site of negotiations between the MTMM, state urban planning practitioners and the local government.